2006
DOI: 10.4049/jimmunol.176.3.1750
|View full text |Cite
|
Sign up to set email alerts
|

CD25+ Regulatory T Cell Depletion Augments Immunotherapy of Micrometastases by an IL-21-Secreting Cellular Vaccine

Abstract: IL-21 is an IL-2-like cytokine, signaling through a specific IL-21R and the IL-2R γ-chain. Because the TS/A mammary adenocarcinoma cells genetically modified to secrete IL-21 (TS/A-IL-21) are strongly immunogenic in syngeneic mice, we analyzed their application as vaccine. In mice bearing TS/A-parental cell (pc) micrometastases, vaccination with irradiated TS/A-IL-21 cells significantly increased the animal life span, but cured only 17% of mice. Spleen cells from cured mice developed CTL activity and produced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 47 publications
0
77
1
1
Order By: Relevance
“…Consistently, a decreased number and/or defective activity of Treg has been documented in autoimmune and allergic diseases (10). In contrast, Treg may sabotage effective immune responses against microbes and tumors (7,8).…”
Section: Il-21 Counteracts the Regulatory T Cell-mediatedmentioning
confidence: 88%
See 3 more Smart Citations
“…Consistently, a decreased number and/or defective activity of Treg has been documented in autoimmune and allergic diseases (10). In contrast, Treg may sabotage effective immune responses against microbes and tumors (7,8).…”
Section: Il-21 Counteracts the Regulatory T Cell-mediatedmentioning
confidence: 88%
“…Although they were initially described to modulate self-tolerance and to protect against autoimmunity, more recent studies have suggested that Treg may also be implicated in suppressing immune responses in infective and neoplastic diseases (7,10). Concomitantly, several authors have shown that Treg activity can be differently modulated by inflammatory molecules, bacterial products, and tumor-derived molecules, thus raising the possibility that we can either enhance or inhibit Treg function for therapeutic purposes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…En effet, de nombreux groupes ont montré dans des études indépendantes que la transfection de l'ADNc codant pour l'IL-21 dans des cellules tumorales murines (issues de cancer du côlon, de mélanome, de fibrosarcome, de cancer mammaire, de cancer de la vessie, de gliome, de carcinome rénal et de neuroblastome) ralentit leur croissance ou entraîne le rejet total de ces tumeurs [4]. De plus, une straté-gie vaccinale, via l'injection de cellules tumorales exprimant l'IL-21 et irradiées dans un modèle murin d'adénocarcinome mammaire, a démontré un allongement de la survie de ces souris [5]. Des résultats identiques sur la réduction de la croissance tumorale et la survie des souris ont été obtenus dans les modèles B16 de méla-nome ou de fibrosarcome, en présence d'un plasmide codant pour l'IL-21 [7].…”
Section: éTudes Précliniques Utilisant L'il-21unclassified